2019
DOI: 10.2172/1601808
|View full text |Cite
|
Sign up to set email alerts
|

Initial Development of an Improved Creep-Fatigue Design Method that Avoids the Separate Evaluation of Creep and Fatigue Damage and Eliminates the Requirement for Stress Classification

Abstract: 60439. For information about Argonne and its pioneering science and technology programs, see www.anl.gov.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(21 citation statements)
references
References 11 publications
1
20
0
Order By: Relevance
“…where is a constant and can be determined from creep-fatigue test data. This model was found to reasonably capture the trend of creep-fatigue experimental data reported in [10] for Alloy 617 at 950°C. Assuming some general inverse power dependence of the cyclic life on elastic follow up Equation 2.2 can be modified to:…”
Section: Modified Coffin-shift Modelsupporting
confidence: 57%
See 4 more Smart Citations
“…where is a constant and can be determined from creep-fatigue test data. This model was found to reasonably capture the trend of creep-fatigue experimental data reported in [10] for Alloy 617 at 950°C. Assuming some general inverse power dependence of the cyclic life on elastic follow up Equation 2.2 can be modified to:…”
Section: Modified Coffin-shift Modelsupporting
confidence: 57%
“…Previous work [10] demonstrated that the base Coffin-shift model exaggerates the effect of hold time on cyclic life when compared with Alloy 617 creep-fatigue experimental data at 950°C. Fundamentally, stress in the material relaxes under creep-fatigue loading and for a long enough hold time will reach to a point where it accumulates negligible creep damage.…”
Section: Modified Coffin-shift Modelmentioning
confidence: 98%
See 3 more Smart Citations